Adolescent Externalizing Problems: Contributions of Community Crime Exposure and Neural Function During Emotion Introspection in Mexican‐Origin Youth. (28th October 2017) - Weissman, David G.; Gelardi, Kristina L.; Conger, Rand D.; Robins, Richard W.; Hastings, Paul D.; Guyer, Amanda E.
Abstract : Models of the etiology of adolescent antisocial behavior suggest that externalizing problems may reflect a susceptibility to crime exposure and a diminished capacity for emotion introspection. In this study, adolescents of Mexican origin completed a neuroimaging task that involved rating their subjective feelings of sadness in response to emotional facial expressions or a nonemotional aspect of each face. At lower levels of neural activity during sadness introspection in posterior cingulate and left temporoparietal junction, and in left amygdala, brain regions involved in mentalizing and emotion, respectively, a stronger positive association between community crime exposure and externalizing problems was found. The specification of emotion introspection as a psychological process showing neural variation may help inform targeted interventions to positively affect adolescent behavior.